2023
DOI: 10.1038/s41588-022-01279-6
|View full text |Cite
|
Sign up to set email alerts
|

Genome-wide RNA polymerase stalling shapes the transcriptome during aging

Abstract: Gene expression profiling has identified numerous processes altered in aging, but how these changes arise is largely unknown. Here we combined nascent RNA sequencing and RNA polymerase II chromatin immunoprecipitation followed by sequencing to elucidate the underlying mechanisms triggering gene expression changes in wild-type aged mice. We found that in 2-year-old liver, 40% of elongating RNA polymerases are stalled, lowering productive transcription and skewing transcriptional output in a gene-length-dependen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
69
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 77 publications
(72 citation statements)
references
References 79 publications
3
69
0
Order By: Relevance
“…Recent research, including my own, has revealed that as an organism ages, its transcriptome changes in a manner that is informed by the lengths of transcript molecules. This relationship between transcript length and aging has been first observed by the lab of Jan Hoeijmakers 8 , and since then been described for C. elegans 9 , fruit flies 10 , killifish 11 , mice 8,9,[11][12][13] , rats 11 , and humans 8,11,14 . In most cases, the correlation between transcript length and age-dependent change is negative, although some tissues and cell types exhibit a positive correlation 11 .…”
Section: Introductionmentioning
confidence: 72%
See 3 more Smart Citations
“…Recent research, including my own, has revealed that as an organism ages, its transcriptome changes in a manner that is informed by the lengths of transcript molecules. This relationship between transcript length and aging has been first observed by the lab of Jan Hoeijmakers 8 , and since then been described for C. elegans 9 , fruit flies 10 , killifish 11 , mice 8,9,[11][12][13] , rats 11 , and humans 8,11,14 . In most cases, the correlation between transcript length and age-dependent change is negative, although some tissues and cell types exhibit a positive correlation 11 .…”
Section: Introductionmentioning
confidence: 72%
“…There are many reviews on organismal 63,64 and molecular damage 39,[65][66][67][68][69] , but it is challenging to find a well-cited review on the various types of transcript damage that occur during biological aging. These damages extend beyond premature termination 9 and include intron retention 27,28 , oxidative damage 70 , and lost synchronization toward the circadian rhythm 71 . It is surprising how few reviews discuss transcript damages 22,39,72,73 , given that research by Lorena Harries and colleagues 74 found that out of 1,065 considered biological and metabolic pathways, six of the seven pathways significantly associated with age in human peripheral blood leukocytes are related to RNA metabolism.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…It will be interesting to investigate if a similar reduction of TC-NER capacity can be measured in aging tissues of e.g. mouse models of aging, as accumulating DNA damage leading to transcription stress is considered one of the driving forces of the aging process (22, 64).…”
Section: Resultsmentioning
confidence: 99%